Developing Problem-Solving Based Assessment to Stimulate Critical Thinking and Creativity of Students’ Writing Skill - Hidayat, Rifki Nurlaili; Rukmini, Dwi; Linggar Bharati, Dwi Anggani (English Education Journal, 2019)
This study was focused on the issues related to the development of problem-solving based assessment model especially in term of writing assessment to stimulate the critical thinking and creativity of the students. Research and Development (R&D) was used as a research design in this study. The subjects of this study were the students of X MIPA 6 at SMA Sultan Agung 1 Semarang in the academic year of 2017/2018. Questionnaire, interview, observation checklist, and tests were used as the instruments in collecting the data. In addition, the researchers collaborated with the teacher in developing the problem-solving writing assessment module. The result of this study revealed that there was a significant improvement of the students’ writing skill, critical thinking skill, and creativity skill. It was proven by the mean score results of the pre-test and post-test. The students’ score improvement of the writing skill was 47.83 to 70.83, and critical thinking and creativity skill was 42.67 to 60.13. Moreover, the paired sample t-test results showed that there was significant different between the result of pre-test and post-test. In conclusion, the problem-solving based assessment is applicable to stimulate the critical thinking and creativity of the students’ writing skill.